The Effect of Myofascial Release Iliotibial Band on Reducing Pain and Increasing Functional Activity in Knee Osteoarthritis - Rustiana Kusumawati, Yoni; Utomo, Budi (Jurnal Keterapian Fisik, 2024)
Background: Knee osteoarthritis is the most common case suffered by elderly women. The population at high risk of experiencing knee osteoarthritis is women at 18% compared to men at around 9.6% worldwide, older age, excessive body weight, and having had a knee injury or having had previous knee surgery. Methods: The design of this study was a two-group pre-and post-test design. The research compares the effect of the myofascial release of the iliotibial band on reducing pain and increasing functional activity in knee osteoarthritis. The research subjects were all clients who had been diagnosed with osteoarthritis by a doctor. Results: The results of the test for the difference in pain scores with VAS before and after treatment in group 1 showed a value of p = 0.000 or a value of p < 0.05, while the functional ability scores with WOMAC before and after group 1 treatment showed a p-value = 0.000 or a p-value < 0.05, which means that there was an effect of standard therapy on reducing pain and increasing functional activity in osteoarthritis knees in group 1 so that the hypothesis was accepted. Conclusion: There is a difference in effect between standard therapy and standard therapy plus myofascial release of the iliotibial band to increase functional activity in knee osteoarthritis. There is a difference in the effect of standard therapy and standard therapy plus myofascial release iliotibial band on increasing functional activity (p = 0.00) in knee osteoarthritis.